Local destabilization, rigid body, and fuzzy docking facilitate the phosphorylation of the transcription factor Ets-1 by the mitogen-activated protein kinase ERK2 - Piserchio, Andrea (Proc Natl Acad Sci U S A, 2017)
Mitogen-activated protein (MAP) kinase substrates are believed to require consensus docking motifs (D-site, F-site) to engage and facilitate efficient site-specific phosphorylation at specific serine/threonine-proline sequences by their cognate kinases. In contrast to other MAP kinase substrates, the transcription factor Ets-1 has no canonical docking motifs, yet it is efficiently phosphorylated by the MAP kinase ERK2 at a consensus threonine site (T38). Using NMR methodology, we demonstrate that this phosphorylation is enabled by a unique bipartite mode of ERK2 engagement by Ets-1 and involves two suboptimal noncanonical docking interactions instead of a single canonical docking motif. The N terminus of Ets-1 interacts with a part of the ERK2 D-recruitment site that normally accommodates the hydrophobic sidechains of a canonical D-site, retaining a significant degree of disorder in its ERK2-bound state. In contrast, the C-terminal region of Ets-1, including its Pointed (PNT) domain, engages in a largely rigid body interaction with a section of the ERK2 F-recruitment site through a binding mode that deviates significantly from that of a canonical F-site. This latter interaction is notable for the destabilization of a flexible helix that bridges the phospho-acceptor site to the rigid PNT domain. These two spatially distinct, individually weak docking interactions facilitate the highly specific recognition of ERK2 by Ets-1, and enable the optimal localization of its dynamic phospho-acceptor T38 at the kinase active site to enable efficient phosphorylation.